An exploration of the experiences and perceptions of community college leaders in the combined role of vice president for academic and student affairs - Broadie, Paul, author; Kuk, Linda, advisor; Foley, Jeffrey, advisor; Anderson, Sharon, committee member; Scott, Malcolm, committee member (Colorado State University. Libraries, 2014)
This study provided a view into the world of individuals serving in the role of vice president of academic and student affairs. Collaboration between academic affairs and student affairs has emerged in the literature as critical and essential for colleges to holistically and effectively address the needs of the institution and their stakeholders (Janey, 2009; Kezar, 2009, 2009a; Pace, Blumreich, & Merkle, 2006). The research revealed that some community colleges adopted an organizational structure that merged the two areas together in hopes of addressing fiscal constraints and fostering collaboration (McClellan, 2004; Price, 1999). This study addressed the gap in the literature that existed regarding the experiences, leadership, and perspectives of those serving in the joint position. Twelve individuals from community colleges across the United States were selected to participant in this study. Utilizing interpretative phenomenological analysis (IPA) five major themes arose; evolution, communication and collaboration, leadership, faculty background, and workload. The findings revealed that communication was an essential element in promoting collaboration, leadership effectiveness, and removing silos that existed between the two areas. Collaboration was perceived to be strengthened as a result of merging the two areas under one leader and uniting them across a common theme. The findings shed light on the critical role of effective leadership and the strategies utilized by participants to unite the two areas and advance the institutional mission. The importance of having experience as a faculty member and a clear understanding of the role of faculty emerged as an influential factor of the leader's ultimate success and acceptance. Workload issues emerged as the most perceived challenge of the position. This study concluded that while there may be many benefits to the merged model the workload challenges and the culture of the institution should not be overlooked. Moreover, regardless of the organizational structure adopted by an institution leadership appeared to be the factor most influential in uniting the two areas, advancing the institutional priorities, and promoting a centralized collaborative focus on student learning and success. Readers of this study may learn and benefit from the reflections, experiences, perceptions and ultimately the recommendations of the participants.
Keywords: academic affairs leadership; collaboration; leadership; merged leadership; organizational structure; student affairs leadership